2020
DOI: 10.36941/ajis-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Audit Report Lag: Evidence from Indonesia

Abstract: This study intends to reveal the influence of firm size, profitability, solvability, and size of the public accounting firm on audit report lag (ARL). The object of this research is mining firms listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. Samples were chosen by purposive sampling method, uses secondary data with 96 samples, and applies multiple linear regression for data analysis. The finding of this research indicates that the solvability and size of public accounting firms influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 8 publications
2
7
2
10
Order By: Relevance
“…The findings of this study do not support the findings of (Shofiyah & Wilujeng Suryani, 2020), (Sudradjat et al, 2022), (Diana & Hidayat, 2022) which contend that the size of the company does not always significantly affect the delay in the release of audit reports. The findings of this study, however, are consistent with those of (Satyawan & ahmmi, 2020), (Machmuddah et al, 2020), who found that the magnitude of the company size always indicate how short an organization's audit report lag will be.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 91%
“…The findings of this study do not support the findings of (Shofiyah & Wilujeng Suryani, 2020), (Sudradjat et al, 2022), (Diana & Hidayat, 2022) which contend that the size of the company does not always significantly affect the delay in the release of audit reports. The findings of this study, however, are consistent with those of (Satyawan & ahmmi, 2020), (Machmuddah et al, 2020), who found that the magnitude of the company size always indicate how short an organization's audit report lag will be.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 91%
“…Semakin besar ukuran KAP cenderung memberikan audit yang berkualitas dan tepat waktu untuk mempertahankan reputasinya di lingkungan bisnis klien. Berdasarkan penelitian Machmuddah et al (2020), ukuran suatu KAP berdampak negatif signifikan pada audit reporting lag sedangkan menurut penelitian Utami et al (2018), ukuran KAP tidak berdampak signifikan terhadap audit repot lag.…”
Section: Pendahuluanunclassified
“…Compliance Theory. Teori kepatuhan berdasarkan Machmuddah et al (2020) adalah teori yang menyatakan setiap perusahaan harus mematuhi aturan karena otoritas pembuat hukum mempunyai wewenang dalam mengatur perilaku (normative commitment through legitimacy). Teori kepatuhan dibagi menjadi dua pandangan yaitu instrumental dan normatif.…”
Section: Kajian Teoriunclassified
See 2 more Smart Citations